Design and simulation investigation of si3n4 photonics circuits for wideband on-chip optical gas sensing around 2 µm optical wavelength - Koompai, Natnicha; Chaisakul, Papichaya; Limsuwan, Pichet; Roux, Xavier Le; Vivien, Laurent; Marris-Morini, Delphine (My University, 2021)
We theoretically explore the potential of Si3N4 on SiO2 waveguide platform toward a wideband spectroscopic detection around the optical wavelength of 2 µm. The design of Si3N4 on SiO2 waveguide architectures consisting of a Si3N4 slot waveguide for a wideband on-chip spectroscopic sensing around 2 µm, and a Si3N4 multi-mode interferometer (MMI)-based coupler for light coupling from classical strip waveguide into the identified Si3N4 slot waveguides over a wide spectral range are investigated. We found that a Si3N4 on SiO2 slot waveguide structure can be designed for using as optical interaction part over a spectral range of interest, and the MMI structure can be used to enable broadband optical coupling from a strip to the slot waveguide for wideband multi-gas on-chip spectroscopic sensing. Reasons for the operating spectral range of the system are discussed.
Keywords: Multi-mode interferometer; Short-wave infrared; Si3N4 on SiO2